Contribution of coastal seiches to sediment transport in a microtidal semi-enclosed bay - Seo, Jun Young; Choi, Byoung-Ju; Choi, Sun Min; Ryu, Jongseong; Ha, Ho Kyung (Frontiers in Marine Science, 2024)
Moorings and axial surveys using acoustic Doppler current profilers in microtidal Masan Bay were conducted to reveal impacts of coastal seiches on sediment behaviors. The hydrodynamic circulation in the bay was dominated by sluggish tidal and residual currents, with which the coastal seiches with a 1-h period were detected. The coastal seiches velocity (useiche) accounted for approximately 30% of the total velocities, causing back-and-forth water motions along the channel. This was insufficient to resuspend bed sediments without external forcings. Nevertheless, it influenced the suspended sediment concentration (SSC) of turbidity maximum (~40 mg l−1) at the central part of bay, showing SSC anomaly of 8 mg l−1. Although the seiche-induced sediment fluxes were only 1% of the total fluxes due to offsetting effect of bidirectional flows, they reached up to 0.040×10−3 kg m−2 s−1 at each pulse of coastal seiches. Repetitive coastal seiches lifted the sediment particles to the upper layer where they would not have risen if not for seiche vertical motion. However, the distance that the coastal seiches can transport the suspended sediments was too short compared to their transportable amounts. Even if sediment particles within turbidity maximum were advected by coastal seiches, they could not leave the region. This process was intensified toward the land because the useiche slowed down the further as it moved away from the node. As long as the bed sediments were resuspended, the coastal seiches were expected to enhance the potential for water pollution by causing repetitive sediment redistribution.